MAGNETIC RESONANCE AND PATHOMORPHOLOGICAL FEATURES OF PLACENTAL LESIONS IN PLACENTAL INSUFFICIENCY - Ирина Сергеевна Мурзина; Наталья Викторовна Путилова; Максим Николаевич Зырянов (The Publishing House Medicine and Enlightenment, 2023)
Magnetic resonance imaging (MRI) of the placenta has been part of the clinical practice of obstetricians and gynecologists and perinatologists for many years. Many studies have shown that pregnancy complicated by placental insufficiency (PN) is associated with an increased risk of perinatal complications. The aim of the research - to conduct a comparative analysis of the results of MR and pathomorphological examination of placentas in patients with placental insufficiency. Materials and methods. An open longitudinal cohort comparative study was conducted. The main group (n = 140) consisted of patients with pregnancy complicated by PN, at 28-36 weeks gestation and afterbirth. The comparison group (n = 30) included patients with the physiological course of pregnancy at the gestation period of 28-36 weeks and afterbirth. All patients underwent ultrasound and MR examination of placentas before delivery, as well as pathomorphological features of placentas were analyzed. Results. The history of the patients of the main group was statistically significantly more likely than that of the patients of the comparison group to include non-developing pregnancy (χ2 14.003; OR 6.688; 2.218-20.166; p < 0.05), medical abortion (χ2 8.102; OR 3.181; 1.048-9.654; p < 0.05), surgical delivery (χ2 4.509; OR 3.600; 1.034-12.977; p < 0.05) and diseases of the endocrine (χ2 17.077; OR 6.370; 2.446-16.590; p < 0.05) and urinary systems (χ2 4.318; OR 4.318; 0.976-19.095; p < 0.05). According to the MRI study, heterogeneity of the placenta structure was recorded significantly more often in the main group than in the comparison group (OR 6,632; 1,513-29,067; p < 0.05). A small volume of placentas was also diagnosed significantly more often in patients of the main group than in patients of the comparison group (OR 6,304; 0.82-48.479; p < 0.05). Areas of diffusion restriction were identified only in the main group in 15.7 % of cases. The pathomorphological study of placental tissue in the patients of the main group allowed to establish morphological criteria for PN: a decrease in placental mass, delayed maturation of chorionic villi, combined vascular circulatory disorders, which corresponds to the picture of changes according to MRI data. Conclusions. In the patients of the main group, according to MRI and pathomorphological examination, the most important placental lesions were ischemic and hemorrhagic lesions with a decrease in the volume of placental tissue. The conducted study proves that the revealed structural changes of the placenta according to MRI correlate with the data of pathomorphological examination.